Mitotic spindle: Focus on the function of huntingtin. - Godin, J.D.; Humbert, S. (International Journal of Biochemistry & Cell Biology, 2011)
Mitotic spindle assembly and orientation are tightly regulated to allow the appropriate segregation of genetic material and cell fate determinants during symmetric and asymmetric divisions. Microtubules and many proteins including the dynein/dynactin complex and the large nuclear mitotic apparatus NuMA protein, are fundamental players in these mechanisms. A recent study reported that huntingtin regulates spindle orientation by ensuring the proper localization of the p150(Glued) subunit of dynactin, dynein and NuMA. This function of huntingtin is conserved in Drosophila. Among other events, spindle orientation influences the fate of daughter cells. In agreement with this, huntingtin changes the direction of division of mouse cortical progenitors and promotes neurogenesis in the neocortex. We will also discuss the involvement of mitotic spindle components in neuronal disorders.